Clinical and laboratory alterations in horses during immunization with snake venoms for the production of polyvalent (Crotalinae) antivenom - Angulo Ugalde, Yamileth (1997)
Six horses were immunized with the venoms of Bothrops asper, Crotalus durissus durissus and Lachesis muta stenophrys for the production of polyvalent (Crotalinae) antivenom. During the immunization, clinical and laboratory alterations were evaluated in these animals, and the development of humoral immune response was followed. Only moderate local tissue changes (edema, abscesses, fistules and fibrosis) were observed in these animals, whereas no systemic alterations occurred. Regarding laboratory tests, there was a drop in hemoglobin concentration and hematocrit, together with an increment in total serum protein. Horses developed a moderate leukocytosis, with increments in polymorphonuclear leukocytes and lymphocytes. No significant changes were observed in prothrombin time or platelet count. There were no alterations in serum lactic dehydrogenase and gamma glutamyl transferase activities, whereas minor increments in creatine kinase and alanine aminotransferase activities were observed, together with a decrease in aspartate aminotransferase. All these changes occurred after the injection of 9 mg venom, when sodium alginate was first used as adjuvant. Creatinine levels had a small increment, although no changes were observed in urea levels or in the urea/creatinine ratio. An important individual variability was observed in the humoral immune response, as judged not only by enzyme-linked immunosorbent assay, but also by assessing the neutralization of the indirect hemolytic activity of venoms.